Neuroscience of Aggression - Miczek, Klaus A.; Meyer-Lindenberg, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This volume assembles the leading aggression researchers both at the preclinical and clinical level. They review the current state of knowledge about neural mechanisms of aggressive behavior and point to the need for innovative methodologies to further our understanding of this greatly understudied set of behaviors.
Neurogenetics of Aggressive Behavior – Studies in Rodents -- Neurogenetics of Aggressive Behavior – Studies in Primates -- Glucocorticoids and Escalated Aggressive Behavior.- Models of Female Aggression – Prefrontal Cortex.- Nitric Oxide, Serotonin and Aggression -- Hypothalamus and Aggressive Behavior -- Vasopressin-Serotonin Interactions in Aggressive Behavior -- Dopamine-oxytocin: Attachment and Conflict -- Stress and violence.- Gene-environment interactions and violence.- MAO-A and genetic risk for violence -- The development of violent behavior in humans -- Schizophrenia and violence.- Psychopathy -- Violent and callous behavior in children -- Aggression in Children and Adolescents- Alcohol and Aggression.
Keywords: Neurosciences; Psychopharmacology; Psychiatry; Neurosciences; Psychopharmacology; Psychiatry